Fertility and carbon stock in pasture and forest environments in the Southern Amazon - Fernando L. Silva; Marcus H. M. e Silva; Ernandes S. Oliveira-Júnior; Marta López-Alonso; Maria A. P. Pierangeli (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Inadequate management of pasture soils in the Amazon has resulted in a predominance of degraded pastures. Considering the natural characteristics of this region can favor more appropriate strategies for sustainability, the objective of this study was to evaluate the differences in the chemical and physical attributes of pasture and forest soils in the Southern Amazon and to identify the most sensitive attributes of their fertility. Additionally, this study suggests appropriate management practices for sustainable pastures. Soil samples from the 0 to 0.20 m layer were analyzed to determine pH, exchangeable bases (calcium, magnesium, and potassium), exchangeable aluminum, potential acidity, phosphorus, organic carbon, bulk density, and texture. Pasture soils had a higher pH, calcium content, and bulk density than forest soils. However, the pasture soils had lower phosphorus and organic matter content. The soil organic carbon stocks were also lower in pasture soils, with levels 0.8 to 12 Mg ha-1 lower than in forest soils. The fertility attributes most sensitive to soil management in these pastures were phosphorus, pH, organic carbon, and bulk density. The lack of nutrients and soil and water conservation practices have contributed to the degradation of these pastures. Therefore, the recommended management for these pastures should aim to improve the organic matter content, reduce compaction, and replenish and cycle nutrients.